Pengaruh Fasad dan Elemen Lain terhadap Kenyamanan Thermal Masjid Istiqlal Jakarta - Mahfud Ragilsa Hariadi; Yonav Partana; Lia Rosmala Schiffer (Jurnal Arsitektur Wastu Padma, 2024)
This research is intended to determine the effect of the facade on the thermal comfort of the Istiqlal Mosque. The urgency of this research is to find an efficient method of managing thermal comfort by taking into account the existence of building elements. The research method used is quantitative by collecting primary data and secondary data through thermal measurements. From the measurement results, it is known that the presence of a facade has a major influence on the formation of thermal comfort in a mosque building. This is because the open facade system allows for smooth air circulation, thus creating cool air. Apart from that, there is an environment and spatial arrangement in the mosque that supports the circulation system, namely the existence of an open space in the middle of the building as an air circulation valve that supports the environmental ventilation system.